Investigating the behaviour change techniques and Motivational Interviewing techniques in Physical Activity Counselling sessions. (May 2018) - Gagnon, Jean-Christian; Fortier, Michelle; McFadden, Taylor; Plante, Yannick
Abstract: Objectives: The present study investigated the content and relational style of a Physical Activity Counselling (PAC) intervention, taught in universities across Canada and applied by Kinesiologists working in primary care. The preliminary objective was to determine whether a new taxonomy of Motivational Interviewing (MI) techniques could be used as a reliable method for reporting interventions. The main purpose was to provide an initial description of PAC sessions through the identification of behaviour change techniques (BCTs) and MI techniques. Design: Descriptive observational study. Methods: Twenty-two videotaped PAC sessions delivered by 11 student-counsellors were double coded. The Behaviour Change Technique Taxonomy v1 and the table of MI techniques were applied to rate the presence of BCTs and MI techniques in PAC sessions. Results: Analyses revealed outstanding inter-rater agreement scores for the identification of BCTs (κ = .77, PABAK = .94) and MI techniques (κ = .81, PABAK = .85). Overall, 29 BCTs and 27 MI techniques were reliably identified across the sample, with an average of 5.7 BCTs and 9.5 MI techniques documented per session. The BCT categories of Goals and planning and Social support were emphasized, whereas the Engaging and Evoking techniques of MI predominated in the analysis. Conclusions: This study shows that the table of MI techniques is a reliable method to report the components of MI interventions such as PAC. Moreover, the study offers a detailed account of content and relational techniques applied in PAC sessions. Findings are particularly relevant to PAC trainers and practitioners. Future directions are discussed. Highlights: Content and relational style of a Physical Activity Counselling (PAC) intervention. First test of the table of MI techniques to report components of an MI intervention. The table of MI techniques is a reliable method for reporting intervention components. Complementary methods to the BCTTv1 should be used to report interventions more fully.